Notarial Practice Treatises in the Libraries of XVIII c. Neogranadino Scribes (2016)
Among the personal libraries of numerary and cabildo scribes during the XVIII c. in the New Kingdom of Granada, we find the presence of forms, treatises or practical manuals inscribed in the tradition of european juridicial “ars notariae” literature, which exercised a fundamental function in the social and economic development of American cities, this task that has been scarcely studied by Colombian historiography. This study analyzes the Post Mortem Inventaries of the scribes Jacobo Facio Lince, Mariano Bueno, Juan Andrés Sandoval and Joaquín Sánchez de la Flor, who exercized their practice in the cities of Medellín, Cartago and Popayán. After a characterization of the personal library archives of these scribes, this study focuses on the individual description of the notarial treatises found, and their circulation in the Indies.